PERSEPSI APARATUR SIPIL NEGARA TERHADAP PENGGUNAAN JASA BANK SYARIAH (STUDI PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN LOMBOK TIMUR) - Imamuddin Imamuddin; Musawar Musawar; Zaenudin Mansyur (Nusantara Hasana Berdikari, 2021)
This study generally aimed to determine the perception of the State Civil Apparatus on the use of Islamic banking services at the Office of the Ministry of Religion of East Lombok Regency. This research was a field researchwith qualitative approach. The source of data was the State Civil Apparatus at the Office of the Ministry of Religion, East Lombok Regency. Data collection was done using observation, interview and documentation techniques. Furthermore, data processing and analysis techniques were carried out through four stages, such as data reduction, data display, conclusion drawing and verification and validity of the data. The study unveiled thatthe State Civil Apparatus perceived the use of Islamic banking services in terms of knowledge and attitudes due to the services provided by the banks and administrative costs which were cheaper. In addition, employees knew that Islamic banks are free of usury, and there are contracts and a profit-sharing system as they are not detrimental and burdened the parties. The perception factor of the State Civil Apparatus in using Islamic banking services cannot be separated from the organizational culture where the employees work. In particular, the State Civil Apparatus used conventional bank services because of the decision of the authoritiestoequalize the accounts for receiving the salaries. The results of the study indicated that the State Civil Apparatus of the Ministry of Religion of the East Lombok Regency remained used the services of conventional banks more than the Islamic banks.